Management Accounting Practices in Egypt A Transitional Economy Country - Sherine Farouk Abdel Al; John D. Mclellan (Journal of Accounting, Business and Management (JABM), 2011)
This study focuses on the adoption rate of management accounting practices by two hundred and fifteen Egyptian manufacturing companies and the ranking by managers of the benefits derived from the practices. Egypt has never been studied to determine the current status of adopted management accounting practices by manufacturers. This study employs the cultural approach using Hofstedes four dimensions of the cultural orientation of a country, to develop hypotheses regarding the choice of management accounting practices used by Egyptian organizations. Hofstede developed an index to represent each of these four dimensions for fifty countries. Egypt scored as having a high degree of power distance and uncertainty avoidance and a low degree of individualism and masculinity. A questionnaire was developed and the survey was conducted by personal interviews of senior financial managers of manufacturing companies listed on the Egyptian stock exchange.Results indicate that Egyptian manufacturing organizations still retain and believe in the benefits derived from using traditional management accounting practices as they fit well with managing in an unstable economy. However, results also show that Egyptian managers have started recognizing the benefits of some of the more advanced management accounting practices.